Implementasi Prinsip Takaful dalam Asuransi Syariah : Analasis Perspektif Surah Al-Maidah Ayat : 2 - Ahmad Farhan; M.Fikri Ariga (Journal Research of Economic and Bussiness, 2026)
Takaful, which means mutual protection, serves as a mechanism whereby individuals or groups help each other in the face of unforeseen risks. This verse emphasizes the importance of helping each other in goodness and piety, which is at the core of the takaful concept. In the context of everyday life, this principle encourages individuals to play an active role in the community, support each other, and avoid harmful behavior. Through education and public awareness of takaful products, it is hoped that participation in the system can increase, thereby creating stronger social solidarity. In this journal, we can also see the importance of openness and honesty in every community interaction, so that trust between the community and takaful organizers can be maintained. Keyword : Takaful, Sharia, Society, Islam